THE BUDDHIST ETHICS WITH NURSING INTERVENTION TO RELIEVE STRESS FOR PARENTS OF PEDIATRIC CRITICAL ILLNESS PATIENTS - Klangka, Panuekkaew; bhavanabodhikun, Phrakhru (Journal of Graduate MCU KhonKaen Campus, 2020)
Pediatric critical illness is a life threatening situation. Causing the father and mother to feel stressed and worried which needs help from the nurse. It is acceptable that Buddhist Ethics can relieve stress and heal the illness. This article aim to study 1) the concepts and theories of stress in the views of health science and in the views of Buddhism, 2) nursing intervention for relieve stress stress for parents of pediatric critical illness patients, and 3) application of Buddhist Ethics in nursing practice to relive stress for parents. The study found that; Buddhism mentions stress as suffering. Nurses have to use the nursing process for promote and support parents to have proper stress management. Nursing intervention must have comprehensive and consist with the needs and stress levels of each parents. The application of Buddhist Ethics into nursing science for stress treatment in parents of pediatric critical illness patients include; the 4 Noble Truths, four principles virtuous existence, and the three characteristics of existence. This can be seen that the application of Buddhist Ethics in nursing practice is a good and appropriate method for the modern context of nursing services that can make more efficient in nursing services.